2023
DOI: 10.2147/idr.s418681
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Induced Wound Infections Which Antimicrobial Resistance, Methicillin- and Vancomycin-Resistant: Assessment of Emergence and Cross Sectional Study

Abstract: Background Wound infection is a prevalent concern in the medical field, being is a multi-step process involving several biological processes. Methicillin-resistant S. aureus (MRSA) and vancomycin-resistant S. aureus (VRSA) infections often occur in areas of damaged skin, such as abrasions and open wounds. Methods This research aims to light the incidence of MRSA and VRSA in wound swabs, the antimicrobial susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Figure 2b shows the percentage of articles according to food sample type with varying detection methods. Although milk was always included in most articles (13,17,22 in PCR, LFIA, and electrochemical methods respectively), the second is mammals in PCR and LFIA (12 and 11 respectively) but plants mainly feature for electrochemical methods (11). In addition, more common food samples in every detection method accounts for more than half of the articles together.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2b shows the percentage of articles according to food sample type with varying detection methods. Although milk was always included in most articles (13,17,22 in PCR, LFIA, and electrochemical methods respectively), the second is mammals in PCR and LFIA (12 and 11 respectively) but plants mainly feature for electrochemical methods (11). In addition, more common food samples in every detection method accounts for more than half of the articles together.…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus is normally found in birds, meat and milk [16]. S. aureus is one of the common bacteria that display antimicrobial resistance, to antibiotics like methicillin and vancomycin [17][18]. Common symptoms of S. aureus are shown on the skin, as painful red welts and sores [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Another of these antibiotics with high AMR found in this study was lincomycin, with the highest resistance observed in commensal S. aureus (83.3%) and S. pseudintermedius (25.9%), as well as in infection-causing S. aureus (33.3%) isolated from dogs. Most of the cases reporting lincomycin resistance in Staphylococcus strains are from intensive care units [ 85 ] and hospitals [ 84 , 86 ], so the expected results would have been that, as in other studies carried out in different countries such as Portugal [ 72 , 78 ], Brazil [ 68 ], Italy [ 73 ], and China [ 79 ], no resistance to this antibiotic would be observed.…”
Section: Discussionmentioning
confidence: 97%
“…In the new WHO medically important antimicrobial list, quinolones belonged to the highest priority critically important antimicrobials (HPCIAs), antibiotics that should only be used in veterinary medicine when all others have failed [28]. Overall, the AMR of quinolones was around 30%, varying from one Staphylococcus species to another, as seen in different studies [68][69][70]. In particular, levofloxacin and moxifloxacin had the highest AMR in the quinolones group in both dog and cat S. aureus and S. pseudintermedius, regardless of whether they were commensal or infection-causing strains.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research ( Avsar et al, 2016 ) proved that this oil treated second-degree burns in rats more quickly than silver sulfadiazine, exhibiting strong TGF-1 expression and wound closure. Additionally, it has a high concentration of monounsaturated and polyunsaturated fatty acids (with an average value of more than 80%), including oleic acid (50%) and linoleic acid (30%), which have antibacterial properties ( Gharby and Charrouf, 2022 ; Almuhayawi et al, 2023b ; Hussein et al, 2023 ), and argan oil can shield the wound from the outside environment. However, in the present trial, no wounds developed an infection.…”
Section: Discussionmentioning
confidence: 99%